KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS PEMBELAJARAN TEMATIK SISWA KELAS IV - Sulistyani, Dwi; Prasetiyawati, Dwi; Ardiyanto, Asep (JGK (Jurnal Guru Kita), 2019)
Abstract: Effectiveness of the Problem Based Learning Model on Critical Thinking Ability of Class IV Students Thematic Learning. This study aims to know the effectiveness of problem-based learning model of the ability to think critically thematic learning IV grade students. The method used in this research is quantitative research Pre-Experimental design with type one group pretest-posttest design. The subject of the research is IV grade students of SDN Sendangmulyo Blora with a total of 20 students. Based on the results of the analysis show that learning using problem-based learing model is effective to the critical thinking thematic learning IV grade students, it is seen the average pretest which initially is 40 and after doing the posttest the average value is 79. Learning with problem-based learing achieves maximum predefined criterion (KKM) that has been determined that is 65. Keyword : Problem Based Learning, Critical Thinking Ability, Thematic Learning Abstrak : Keefektifan Model Problem Based Learning terhadap Kemampuan Berfikir Kritis Pembelajaran Tematik Siswa Kelas IV. Penelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran problem based learning terhadap kemampuan berfikir kritis pembelajaran tematik siswa kelas IV. Metode yang digunakan dalam penelitian ini adalah penelitian kuantitatif Pre-Experimental design dengan jenis one group pretest-posttest design. Subjek penelitian adalah siswa kelas IV SD Negeri Sendangmulyo Blora dengan jumlah 20 siswa. Berdasarkan hasil analisis menunjukkan bahwa pembelajaran menggunakan model problem based learing efektif terhadap kemampuan berfikir kritis pembelajaran tematik siswa kelas IV, dilihat rata-rata pretest yang awalnya adalah 40 dan setelah melakukan posttest rata-rata nilainya adalah 79. Pembelajaran dengan problem based learing mencapai ketuntasan kriteria maksimal (KKM) yang telah ditentukan yaitu 65. Kata Kunci : Problem Based Learning, Kemampuan Berfikir Kritis, Pembelajaran Tematik